1998
DOI: 10.1021/ja982970g
|View full text |Cite
|
Sign up to set email alerts
|

Self-Folding Cavitands

Abstract: A novel class of resorcinarene-based cavitands 2a − e that fold into a deep (8 × 10 Å dimensions) open-ended cavity by means of intramolecular hydrogen bonds has been synthesized. As follows from the FTIR and 1H NMR spectral data in apolar solvent, a seam of eight intramolecular hydrogen bonds is stitched along the upper rim of the structure 2a − e; the amide CO ... H−N interactions bridge adjacent ringsinterannular bindingand are held in place by the seven-membered intraannular hydrogen bon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
157
0
1

Year Published

1999
1999
2014
2014

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 192 publications
(163 citation statements)
references
References 49 publications
5
157
0
1
Order By: Relevance
“…Therefore, the skeleton may oscillate between two conformations. This kind of behavior has been reported earlier for resorcarene derivatives [35] and resorcarenes: NMR studies have shown that the average C 4v structure symmetry is the result of two interconverting C 2v boat conformers [36]. However, the rate of this change is so fast that severe conformational changes to the macrocyclic ring do not occur and the crown conformation is maintained.…”
Section: Computational Studiessupporting
confidence: 79%
“…Therefore, the skeleton may oscillate between two conformations. This kind of behavior has been reported earlier for resorcarene derivatives [35] and resorcarenes: NMR studies have shown that the average C 4v structure symmetry is the result of two interconverting C 2v boat conformers [36]. However, the rate of this change is so fast that severe conformational changes to the macrocyclic ring do not occur and the crown conformation is maintained.…”
Section: Computational Studiessupporting
confidence: 79%
“…[20] We attributed this to the open-top structure of the cavi- Table 1: Kinetic parameters (DH°, DS°, and DG°2 98 K ) for the kite1-kite2 interconversion, thermodynamic quantities (DH, DS, and DG 298 K ) for the vase!kite equilibrium, and chemical shifts d 298 K (*) of the methine protons of cavitands ox-1a-c, red-1 b, ox-2 b, and red-2 tands [6e, 10] and to their structural flexibility. [21] To address the first issue, we prepared the triptycene-derived diquinone cavitand ox-3 and its reduced form, red-3 ( Figure 5). 1 H NMR studies showed that the conformational properties of cavitands ox-3 and red-3 are very similar to those of cavitands ox-2 a-c and red-2 a-c.…”
mentioning
confidence: 99%
“…The nine-membered diether rings impart flexibility on the cavitand, allowing the walls to draw closer or move farther from the center of the cavity in response to a guest (19). The amide groups of the upper rim stabilize this vase conformation by forming a seam of hydrogen bonds in either a clockwise or counterclockwise orientation (20,21) determined by the handedness of the Nacylbenzimidazole. The plasticity of hydrogen bonds permits extensive ''breathing'' at the upper rim.…”
Section: Resultsmentioning
confidence: 99%